Vloga stereotipov v sodobni slovenski kratki prozi - Bošnjak, Blanka (Jezik in slovstvo, 2005)
The theoretical framework for the role of an actor as a category in prosaic subjectivity was argued by Algirdas Julien Greimas with his actant model, foregrounding the required relation between subject and object. This may result in encountering the problem of stereotypes (Toril Moi) that still appear in modern literature, and are related mainly to the understanding of gender roles or the position of a woman and a man and their relationship within a society. The article focuses on the role of the female figure as a subject of modern Slovene short fiction, reflecting the various possibilities of verbalisation (e.g. the phenomenon of a stereotypical female figure as a seductress and its ironisation, the figure of a devoted wife or of an active woman).
Keywords: Slovene literature; slovenska književnost; kratka proza; stereotipi; ženski liki; literarne študije